Development of Articulate Storyline based Local Content Learning Media to Improve Learning Outcomes of Elementary School Students - Eka Wulandari; Atip Nurharini (Jurnal Penelitian Pendidikan IPA, 2025)
This study uses the Research and Development (R&D) method with the ADDIE development model, which aims to develop Articulate Storyline learning media that can improve learning outcomes of Semarang local content, namely Denok Deblong dance for grade IV elementary school students. The data collection techniques used are test techniques by giving pretests and posttests, and non-test techniques with observation, interviews, documentation, and questionnaires. The data analysis techniques used were normality test, T-test, and N-gain. The results showed that the local content learning media based on Articulate Storyline was categorized as very feasible to use with material validation results of 92.85%, and media validation of 93.75. The paired sample test showed a significance value of 0.001 <0.05 which means there is an influence on student learning outcomes before and after using Articulate Storyline local content media. The results of the small-scale N-Gain test were 0.5257 and large-scale 0.5998 which showed a moderate category. With the results of this study, it can be concluded that Articulate Storyline learning media is feasible and effective in improving the learning outcomes of local content of Denok Deblong dance for grade IV elementary school students.